Pengaruh Peran dari Influencer dan Media Sosial (TikTok) terhadap Minat Beli Produk Kecantikan Wardah di Kalangan Mahasiswi STBM Dua Sudara Bitung - Devie Mathilda Lumentut; Anamawalda Putri Masira (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2026)
In the increasingly developing digital era, the role of influencers on social media has become increasingly significant in influencing consumer behavior and their purchasing intentions. This study aims to quantitatively analyze the relationship between the presence of influencers on social media and consumer purchasing intentions. This research aims to determine how influencers and social media (TikTok) influence the purchasing intentions of Wardah products among female students of STBM Dua Sudara Bitung. This research uses a descriptive quantitative research design. The sample in this study was 77 respondents with a purposive sampling method. In addition, multiple linear regression analysis shows that factors such as age and gender can moderate the relationship between the presence of influencers on social media and purchasing intentions. For example, the millennial generation may be more likely to be influenced by influencers in their purchasing decisions compared to older generations. The data of this study were analyzed using the SPSS program. After the data was tested using a correlation test, the findings in this study obtained a value of 0.717. Then the value in the determination test was 0.000>0.05, which means there is a significant relationship. Furthermore, the results of the simple linear regression test showed that the calculated t-value was greater than the table t-value, indicating significant significance. This means that influencers and social media (TikTok) have a strong influence on Wardah product purchase intention among female students at STBM Dua Sudara Bitung.